Offering Justice: Women's Emancipation in an Islamic Perspective for Gender Equality and Human Rights Liberation - Zahrina Iza Al-Rahman; Muthoifin (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
This research focuses on an in-depth analysis of the concept of women's emancipation from an Islamic perspective, to explore the principles of justice and gender equality taught in Islam, as well as their application in the liberation of women's human rights. Through a qualitative approach and literature review, this study explores Islamic teachings related to women's positions, their rights, and the challenges faced in realizing gender equality. The study also discusses various interpretations of sacred texts that are often considered controversial, to offer a broader and inclusive understanding of women's emancipation in Islam. The results of the study show that Islam, in its essence, advocates for equal rights and justice for all human beings, including women. Islamic teachings on inheritance, education, and the right to marry, for example, are evidence of the principles of justice offered by Islam to women. However, misinterpretations and patriarchal cultural practices have obscured this understanding and often hindered the full realization of women's human rights in Muslim societies. This research suggests the need for wider education and dialogue on the true teachings of Islam related to gender, as well as the importance of reinterpreting sacred texts in a contemporary context to ensure the true emancipation of women and the liberation of their human rights.